Menguatkan Kepercayaan Diri Klien Minoritas: Analisis Hambatan dalam Konseling Multikultural (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Minority clients’ self-confidence is often influenced by various obstacles that arise within the context of multicultural counseling. These obstacles can be internal or external, including experiences of discrimination, social prejudice, language differences, and conflicts related to cultural identity. Counselors who are not sensitive to clients’ cultural and social dynamics risk reinforcing low self-confidence and hindering the counseling process. This study aims to analyze these barriers and identify effective intervention strategies to enhance minority clients’ self-confidence. The method used is a comprehensive literature review of studies related to multicultural counseling, self-esteem, and empowerment of minority clients. The analysis shows that culturally-based counseling approaches, adaptive communication, and the application of empowerment techniques can help clients overcome psychological and social barriers. Additionally, creating an inclusive and emotionally safe counseling environment has been proven to increase client engagement and strengthen self-confidence. This study emphasizes the importance of multicultural training for counselors and the implementation of strategies that respect clients’ cultural identities. The findings provide practical implications for counselors to develop effective interventions that support the psychological well-being of minority clients.